2021
DOI: 10.1002/adfm.202011284
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Methods to Enhance Photovoltaic Effect for Self‐Powered Heterojunction Photodetectors and Their Applications in Inorganic Low‐Dimensional Structures

Abstract: An important class of photoelectronic devices, self‐powered photodetectors, has attracted worldwide attention because of its crucial role in both basic scientific research and commercial/public applications. Thanks to a special synergistic effect, excellent photoelectric properties, and outstanding mechanical stability, the study of heterojunction devices can provide valuable insights and new possibilities for the future of self‐powered photodetectors. This paper reviews the recent years of fundamental researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 167 publications
0
51
0
Order By: Relevance
“…19 Currently, most photodetectors usually require the application of an external bias voltage to prevent the recombination of photogenerated electron-hole pairs, which not only increases equipment size and energy consumption but also limits the long-term application of detectors in unmanned hazardous environments or harsh atmospheres. [20][21][22] Thus, building self-powered photodetectors without any power supply is being widely studied, which meets the demands of next-generation portable and wearable devices. [23][24][25][26][27] So far, self-powered photodetectors have been realized based on the photovoltaic effect with a pn junction, Schottky junction, and heterojunction structure, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…19 Currently, most photodetectors usually require the application of an external bias voltage to prevent the recombination of photogenerated electron-hole pairs, which not only increases equipment size and energy consumption but also limits the long-term application of detectors in unmanned hazardous environments or harsh atmospheres. [20][21][22] Thus, building self-powered photodetectors without any power supply is being widely studied, which meets the demands of next-generation portable and wearable devices. [23][24][25][26][27] So far, self-powered photodetectors have been realized based on the photovoltaic effect with a pn junction, Schottky junction, and heterojunction structure, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The ideality factor, saturation current and barrier height values were calculated and resistance rather than more than unity (Cifci et al, 2018;Kacus et al, 2020) These results can be indicated to good response time according to literature (Hu et al, 2021). These results can be indicated to good response time according to literature (Hu et al, 2021).…”
Section: Methodsmentioning
confidence: 75%
“…These results implied good response time according to literature. [58] The data from I-t graphs were used to calculate various photodetector parameters such as photocurrent, photosensitivity, responsivity, specific detectivity, and noise equivalent power. Their formulas are given in equations from (1) to ( 5).…”
Section: Electrical Characteristics Of the Al/copom/p-si And Al/nipom...mentioning
confidence: 99%